Health risk assessment of textile effluent reuses as irrigation water in leafy vegetable Basella alba - Mashura Shammi; Mohammad Abul Kashem; Md. Mostafizur Rahman; Md. Delwar Hossain; Rashadur Rahman; M. Khabir Uddin (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose The aim of this research was to assess the health risk of textile wastewater reuse as irrigation water on leafy vegetable (Basella alba) by comparing variable growth rate in different ration of wastewater and freshwater irrigation and assess their soil-to-plant transfer factor (TF) and health risk index (HRI). Methods Pot experiments were laid out with five treatments including control with three replications with different irrigation schemes with textile wastewater collected from the untreated point source. The irrigation scheme was, 100 % groundwater as control with four treatments as 75 % groundwater: 25 % wastewater, 50 % groundwater: 50 % wastewater, 25 % groundwater: 75 % wastewater and 100 % wastewater. Results Soil-to-plant TF in different treatments including control were in the order of Pb (1.0â1.7)[Cu (1.3â1.5)[Cd (0.8â1.0)[Zn (0.1â1.1). TF values of Pb and Cu in the range from 1 to 1.7 indicating their accumulation in B. alba plants and their potential health risk by dietary exposure. The HRI for individual metal as well as cumulative HRI of the metals was less than unity (0.33) which indicated the consumption of the vegetables was considered to be safe for one harvest. Conclusion Over many seasons of irrigation with wastewater, level of salinity and heavy metals can accumulate on the agriculture land and their long term consumption may link to a chronic health risk. Hence, consumption of these vegetables on regular basis should be avoided